Patterns of coagulation profiles observed in different trimesters of pregnancy - Olufemi-Aworinde, Joyce K.; Aworanti, Oladapo W.; Ojedokun, Samson A.; Akinbola, Ibukun O.; Agunbiade-Olu, Mobolaji; Akinbola, Abraham I. (International Journal of Research in Medical Sciences, 2023)
Background: The risk of venous thromboembolic events (VTE) is high during pregnancy due to both physiologic changes in pregnancy and the impact of inherited and acquired thrombophilia. Protein S (PS), Protein C (PC) and Antithrombin III (ATIII) deficiencies have been found in some pregnant women with recurrent miscarriages and sudden maternal death. This study aimed to determine the changes in the level of plasma protein C, protein S and antithrombin III levels, its correlation with normal pregnancy. Methods: The study was a comparative cross-sectional study conducted among seventy-five normal pregnant women who were selected using a simple random sampling technique with seventy-five age-matched healthy nonpregnant women. Blood samples were collected for analysis of protein C, protein S and antithrombin III using the enzyme-linked immunosorbent assay method. A semi-structured questionnaire was used as the survey instrument and Statistical analysis of data was done using SPSS version 24. Results: The mean ages of the respondents were 32.6±4.6 and 34.5±6.9 years for the subjects and controls respectively. Natural coagulation inhibitors (NCI) show a gradual decrease across the trimesters of pregnancy. There was a statistical significance in the level of antithrombin III and protein S in the first trimester, p<0.05. When compared with the control of protein S of 4.78±0.65 ng/ml and antithrombin III of 554.16±54.65 ng/mL respectively. Conclusions: It was demonstrated that there was an accompanying reduction of NCI across the trimester compared with the controls. Antithrombin III and protein S have a significant relationship with the gestation periods. Antithrombin III decreased as pregnancy advanced while protein S decreased significantly from the first trimester to the second trimester and was maintained at that level throughout the pregnancy.